Virtue Analysis of Social Forestry in the Public Space Through the Maqashidi Approach - Nur Anis Rochmawati; Rika Leli Dewi Khusaila Rosalnia (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2022)
The granting of forest use rights by the central government to private and state companies, at a later stage creates inequality for residents around the forest. Those who incidentally are the recipients of the earliest ecological damage do not get many opportunities to participate in reaping the resources around them. No wonder, if the economic condition of the surrounding population is still below the poverty line. The Ministry of Environment and Forestry (KLHK) established a program, social forestry. This is an effort to provide legal access to land management in the state forest area of 12.7 million hectares to the community. Based on this description, this article will reveal the extent to which social forestry programs have a positive impact on the environment, both human and natural. As an analytical tool, Abdul Mustaqim’s maqashidi interpretation is projected to explore the maqashidiyah dimensions (maqashid al-Qur’an and maqashid shari’ah) of social forestry by referring to several verses that talk about the theme. For the conclusions, the social forestry program is able to represent the maqashid dimensions of the Qur’an on the freedom and responsibility values. In the maqashid shari’ah dimension, it’s cooperative as an effort to protect the soul (hifdz al-Nafs and protect the environment (hifdz al-bi’ah)